Effectiveness of a digital platform-based implementation strategy to prevent work stress in a healthcare organization: a 12-month follow-up controlled trial - Havermans, Bo M.; Boot, Cécile RL; Brouwers, Evelien PM; Houtman, Irene LD; Heerkens, Yvonne F.; Zijlstra-Vlasveld, Moniek C.; Twisk, Jos WR; Anema, Johannes R.; van der Beek, Allard J. (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVES ': 'Healthcare workers frequently deal with work stress. This is a risk factor for adverse mental and physical health effects. The objective of this study was to investigate the effectiveness of a digital platform-based implementation strategy – compared to a control group – on stress, work stress determinants (ie. psychosocial work factors) and the level of implementation among healthcare workers. ' ' METHODS ': 'By way of matching, 30 teams from a healthcare organization were assigned to the experimental (15 teams; N=252) or wait-list control (15 teams; N=221) group. The experimental group received access to the strategy for 12 months. They were asked to complete the 5-step protocol within six months. The primary outcome was stress (DASS-21) and secondary outcomes were psychological demands, social support, autonomy, and the level of implementation. Questionnaire-based data were collected at baseline, and at 6- and 12-months follow-up. Linear mixed model analyses were used to test differences between the two groups. ' ' RESULTS ': 'In total, 210 participants completed the baseline questionnaire and at least one follow-up questionnaire. There was a significant effect of the strategy on stress in favor of the experimental group [B=-0.95, 95% confidence interval (CI) -1.81 – -0.09]. No statistically significant differences were found for any secondary outcomes. ' ' CONCLUSIONS ': 'The strategy showed potential for primary prevention of work stress, mainly explained by an increase in stress in the control group that was prevented in the experimental group. More research is necessary to assess the full potential of the strategy.
Keywords: controlled trial; digital platform; effect; employee; health care; healthcare; healthcare organization; intervention; occupational stress; organizational; prevention; trial; work stress; work-related stress; worker